Lens-Photovoltaic Cell Coupling in a Holographic Solar Concentration System - Marín-Sáez, Julia; Collado, María Victoria; Chemisana, Daniel; Atencia, Jesús (Jornada de Jóvenes Investigadores del I3A, 2017)
A solar concentration system formed by two holographic cylindrical lenses is proposed. It redirects part of the incident solar spectrum towards a PV cell, concentrating only the cell’s most efficient wavelength range, while the rest is transmitted, not causing overheating. Simulations with one- and two-axes tracking are carried out.